1969
DOI: 10.1063/1.1671385
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of Electronic Excitation Energy in Polyvinyl Carbazole

Abstract: The energy transfer in amorphous polyvinyl carbazole (PVCA) has been studied by fluorescence quenching experiments using perylene, trinitrofluorenone, and hexachloro-p-xylene as guest molecules. The PVCA shows excimer fluorescence. The results are discussed in terms of exciton diffusion and competition between excimer-forming sites and guest molecules for the trapping of excitons. Single-step transfer from the excimer state by dipole resonance is considered as an alternative mechanism of energy transfer; in al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
79
1

Year Published

1971
1971
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 292 publications
(88 citation statements)
references
References 21 publications
8
79
1
Order By: Relevance
“…The PL maximum for PVK at ca 410-415 nm with short-wavelength shoulder, is due to the emission from two different types of the carbazole singlet excimers and also from isolated carbazole groups (at 350-360 nm). Similar spectra for PVK were reported by Klöpffer and Fischer [18] and by Bässler [19], who have argued that in PVK the traps are neutral and probably connected with carbazole dimers yielding excimer states.…”
Section: Photoluminescence and Electroluminescencesupporting
confidence: 66%
“…The PL maximum for PVK at ca 410-415 nm with short-wavelength shoulder, is due to the emission from two different types of the carbazole singlet excimers and also from isolated carbazole groups (at 350-360 nm). Similar spectra for PVK were reported by Klöpffer and Fischer [18] and by Bässler [19], who have argued that in PVK the traps are neutral and probably connected with carbazole dimers yielding excimer states.…”
Section: Photoluminescence and Electroluminescencesupporting
confidence: 66%
“…Kinetic analysis of the monomer and the excimer emission was carried out, where the migration rate of excitation energy k, and the excimer formation rate of an adjacent pair of naphthalene units on the copolymer chain k21 were treated. Observed decay curves and quantum yields were in agreement with those calculated by the kinetic equations, and the rate constants were obtained: k, = 3 x I 0 8 s -1 , k21 = 2 x 10 8 s - Since the first observation of excimer emission in polystyrene/ many spectroscopic investigations of vinyl aromatic polymers have been reported, e.g., poly(vinylnaphthalene ), 2 poly( vinylcarbazole ), 3 and poly(vinylpyrene). 4 In dilute solutions, these polyl!lets show efficient intramolecular excimer formation with the pendant chromophores on the polymer chain.…”
supporting
confidence: 58%
“…Found: C,92.85;H,6.91%;M+,400. I ,3,pentane (I ,3,5-TNPe) was synthesized by the same method as that for 1,5-DN-3-PhPe. 2-Bromonaphthalene was used instead of bromobenzene.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown by the broken line in Figure 4b, the analysis revealed that the PCLG spectrum consisted of three components, and two of these were assigned to components corresponding to sandwich-excimer (face-to-face overlapped excimer with an emission peak at 410 nm), and second excimer (partially overlapped excimer, 380 nm). 12 In contrast, the spectrum for PVK consisted mainly of a broad component attributed to a sandwich excimer. The reason why the spectrum for PCLG exhibits a larger second excimer component can be explained by the difference in side-chain conformation.…”
Section: Resultsmentioning
confidence: 95%